Pengaruh Parameter Proses Freis Terhadap Kekasaran Permukaan Baja Karbon Fasa Ganda - Arifin, Nur Mohammad; Sonief, Achmad As'ad; Atmodjo, Winarno Yahdi (Rekayasa Mesin, 2011)
Dual phase is a new structure at low or medium carbon steel. The structure is obtained from the heating of low or medium carbon steel in the region Î± + Î³ (temperatures between A1-A3), then follow by holding process within a certain time and cooled quickly (quench) in water,brine or oil. The result has a microstructure of martensite and ferrite as well as a few otherstructures. The steel usually has high tensile strength, good elongation and there is no discontinuity yield. The problem is how the influence of parameters milling process on surface roughness the dual phase carbon steel The purpose of this study was to determine the outcome Freis CNC cutting conditions due to the formation process of double and tempering phase that begins with the process of forging (forging) on carbon steel .This study used AISI1045 steel Ã˜16mm x 150mm diameter, which was forged at a temperature of 950oC-900oC to form a rectangular cross section with a size of 10mm x 16mm x 180mm. Dual-phase heating was continued at a temperature of 770ÂºC, arrested at 90 'and cooled rapidly in oil , followed by atempering process 600â°C/30 '. The process of cutting was done by cutting finishing with feeding 0.12; 0.14; 0.16 mm / put and depth of cut 0.4; 0.6; 0.8 mm while roughing cuts by feeding 0.2;0.4; 0.6 mm / put and depth of cut 1.2, 1.4;a1.6amm .The result Depth of cut can affect the deflection. The deflection could be increased by increasing the depth of cut. The results obtained increase the level of surface roughness. On the depth of cut 0.4 mm with feeding 0:16mm / put the value obtained average roughness Ra 0.64 Î¼m, including group N6 roughness when compared with 0.8 mm depth of cut with the same feeding value of average roughness Ra 1.08 Î¼m including N7. Surface roughness increased by feeding could affect the feeding of 0.12 mm / put and 0.16 mm / put, 0.2 mm / put and 0.6 mm /put because the distance from the cutting peak roughness increases, so the roughness of the rough and the process of finishing cuts on carbon steel dual phase is more subtle than on the untreated carbon steel with the same cutting parameters.Keywords: forging, dual phase (dual phase), the cutting parameters